ANALISIS DAMPAK KESADARAN WAJIB PAJAK SANKSI PERPAJAKAN DAN PENGGUNAAN E-SAMSAT TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - fortune, rut; ompusunggu, Hermaya (SCIENTIA JOURNAL, 2022)
The purpose of this study is to determine the impact of taxpayers' understanding and perceptions of tax laws on vehicle tax compliance. The survey was conducted at SAMSAT Batam Center office. The sample size of this survey is 100 respondents, using incremental sampling method. This survey is a quantitative survey. From the results of this study, we can see that knowing the TAIX law has a positive and significant impact on road tax payment compliance at SAMSAT Batam Center Office. This is seen from t count 5.185 > t table 1.189 and sig 0.399, which shows that taxpayer perceived effects sometimes have no significant impact on taxpayer compliance. This can be seen from the t-count value of 2.968 and the sig 0.004 <0> 0.05, which allows us to conclude that the use of e-Samsat has no positive impact on road tax compliance. Keywords : the impact of taxpayer awareness, tax santions, use of E-Samsat on motorvehcile taxpayer comliance